Uncertain times : anthropological approaches to labor in a neoliberal world - Durrenberger, E. Paul, 1943- (University Press of Colorado, 2017)
"The first-ever collection of labor anthropology from around the world, Uncertain Times addresses the theory that traditional labor union organization has been co-opted by the neoliberal policies of corporate capital and become a member service rather than a driver of social movements"--Provided by publisher